Quality of experience and quality of service‐aware handover for video transmission in heterogeneous networks. Issue 5 (22nd February 2019) - Medeiros, Iago; Pacheco, Lucas; Rosário, Denis; Both, Cristiano; Nobre, Jéferson; Cerqueira, Eduardo; Granville, Lisandro
Summary: Heterogeneous networks offer a wide range of multimedia services, such as entertainment, advertising, and video conferences. In this multimedia scenario, users can access video content via heterogeneous wireless networks, such as LTE macro and small cells. Users also expect to receive real‐time videos with Quality of Experience (QoE) support, which is a challenging task due to the great diversity of radio base stations in such heterogeneous environments. In this article, we introduce a Quality of Service (QoS‐)/QoE‐ and Radio‐aware (SER) handover management algorithm for heterogeneous networks to provide video dissemination with QoS/QoE support. SER algorithm considers the analytic hierarchy process (AHP) to adjust the degree of importance of each criterion in order to select the appropriate radio base station that the mobile node must connect, allowing efficient handover decision making for video transmission with high user experience. Simulation results show that the SER algorithm delivered videos with significant improvement on QoE than existing handover algorithms. Abstract : This article proposes a handover management algorithm named SER for heterogeneous networks considering Quality of Experience (QoE), Quality of Service (QoS), and Radio‐aware metrics to provide video dissemination with QoE/QoS support. SER algorithm considers the analytic hierarchy process to adjust the degree of importance of each criterion to select the appropriate radio base station that the mobile node must connect. Simulation results show that the SER algorithm delivered videos with more than 12% better QoE than other existing handover algorithms.